Non-causal relationship of polycystic ovarian syndrome with homocysteine and B vitamins: evidence from a two-sample Mendelian randomization - Su, Nianjun; Li, Jinsheng; Xia, Yubing; Huang, Cuiyu; Chen, Lei (Frontiers in Endocrinology, 2024)
Objective: Previous observational studies have identified a correlation between elevated plasma homocysteine (Hcy) levels and polycystic ovary syndrome (PCOS).This study aimed to determine whether a causal relationship exists between Hcy and PCOS at the genetic level.A two-sample Mendelian Randomization (TSMR) study was implemented to assess the genetic impact of plasma levels of Hcy, folate, vitamin B12, and vitamin B6 on PCOS in individuals of European ancestry. Independent single nucleotide polymorphisms (SNPs) associated with Hcy (n=12), folate (n=2), vitamin B12 (n=10), and vitamin B6 (n=1) at genome-wide significance levels (P<5×10 -8 ) were selected as instrumental variables (IVs). Data concerning PCOS were obtained from the Apollo database. The primary method of causal estimation was inverse variance weighting (IVW), complemented by sensitivity analyses to validate the results.The study found no genetic evidence to suggest a causal association between plasma levels of Hcy, folate, vitamin B12, vitamin B6, and PCOS. The effect sizes, determined through random-effect IVW, were as follows: Hcy per standard deviation increase, OR = 1.117, 95%CI: (0.842, 1.483), P = 0.442; folate per standard deviation increase, OR = 1.008, CI: (0.546, 1.860), P = 0.981; vitamin B12 per standard deviation increase, OR = 0.978, CI: (0.808, 1.185), P = 0.823; and vitamin B6 per standard deviation increase, OR = 0.967, CI: (0.925, 1.012), P = 0.145. The fixed-effect IVW results for each nutrient exposure and PCOS were consistent with the random-effect IVW findings, with additional sensitivity analyses reinforcing these outcomes.Our findings indicate no causal link between Hcy, folate, vitamin B12, vitamin B6 levels, and PCOS.